An assessment of Sn-W-Nb-Ta oxide minerals from the Bugesera district of Rwanda and geological context - Buurman, Innes (My University, 2018)
The Sn‐W‐Nb‐Ta oxide minerals of Rwanda are rarely found in the same area and predominantly occur in different deposits. Gatumba is known for its pegmatite related Nb‐Ta, and Sn mineralisation, Nyakabingo for its hydrothermal vein type W mineralisation, and Rutongo for its hydrothermal vein type Sn mineralisation. Very little geological research has been performed on the Bugesera district in Rwanda. Therefore, the aim of this study is to enhance the knowledge base on the Bugesera district by studying four mining areas (Nyagasagara, Gakurazo, Kageyo and Kageyo Extension) on the Hard Metal Rwanda (HMR) license, their locations relative to regional structures and G4 granites, and the mineral grade at each of the deposits. The mineralogy and mineral chemistry were only studied on the concentrate material from Nyagasagara, for comparison with literature and to determine whether the mineralisation was primary or secondary. The HMR license is located in between the Bugesera granite and the Bugesera syncline fold. Nyagasagara and Kageyo occur adjacent (< 4km) to known large scale structures, granites and/or pegmatites, Gakurazo is located in between Nyagasagara and Kageyo, and the Kageyo Extension is located on the rim of the Bugesera granite. No outcrops of granite and/or pegmatite were observed at any of the sites. The highest mineral grade was recorded at Nyagasagara Tunnel 1 (5.56% cassiterite) with the lowest grade recorded at Kageyo and Kageyo Extension (0.01% coltan). Around 60% of the cassiterite grains from Nyagasagara, reports to the coarser size fraction of +4 mm and +2 mm, with the shape of the grains ranging from angular to very angular. Cassiterite is the only oxide mineral of interest present at Nyagasagara, as confirmed by the whole rock chemistry and optical microscopy on the concentrate samples from Nyagasagara. The mineral chemistry of the cassiterite plots in the rare element granite and pegmatite field on the binary Nb + Ta and Fe + Mn diagram. Most of the cassiterite contains more Nb compared to Ta (Nb>Ta) and minor Fe2O3. The cassiterite also contained numerous coltan inclusions and exsolution products. This study concludes that the HMR license area is situated in a suitable regional geological setting for Sn‐ W‐Ta‐Nb oxide minerals to be found. However, the Nyagasagara deposit is an eluvial deposit consisting of only cassiterite minerals, which have a magmatic origin, believed to be related to rare element granites.
Keywords: Zinc oxide; Nanostructured materials